2022
DOI: 10.1161/circresaha.121.319874
|View full text |Cite
|
Sign up to set email alerts
|

GLP1R Attenuates Sympathetic Response to High Glucose via Carotid Body Inhibition

Abstract: Background: Aberrant sympathetic nerve activity exacerbates cardiovascular risk in hypertension and diabetes, which are common comorbidities, yet clinically sympathetic nerve activity remains poorly controlled. The hypertensive diabetic state is associated with increased reflex sensitivity and tonic drive from the peripheral chemoreceptors, the cause of which is unknown. We have previously shown hypertension to be critically dependent on the carotid body (CB) input in spontaneously hypertensive rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 58 publications
3
52
0
1
Order By: Relevance
“…Figure 6B presents the immunoreactivity of GLP-1R in young and adult animals and the impact of HFHSu on these levels. It should be noted that GLP-1R (red fluorescence) is detected in type I cells and demonstrated here by the colocalization with TH (green fluorescence), in accordance with Pauza et al (2022) . Short-term HFHSu intake or CSN resection in young animals did not modify the percentage of cells immunoreactive to GLP-1R.…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…Figure 6B presents the immunoreactivity of GLP-1R in young and adult animals and the impact of HFHSu on these levels. It should be noted that GLP-1R (red fluorescence) is detected in type I cells and demonstrated here by the colocalization with TH (green fluorescence), in accordance with Pauza et al (2022) . Short-term HFHSu intake or CSN resection in young animals did not modify the percentage of cells immunoreactive to GLP-1R.…”
Section: Resultssupporting
confidence: 88%
“…The CB has been described as a metabolic sensor, and its dysfunction has been associated with metabolic diseases, such as prediabetes and type 2 diabetes ( Ribeiro et al, 2013 ; Conde et al, 2017 ; Conde et al, 2018 ; Sacramento et al, 2020 ). Knowing that insulin ( Ribeiro et al, 2013 ) and GLP-1 ( Pauza et al, 2022 ) are metabolic mediators that activate the CBs, we evaluated the effect of HFHSu consumption, ageing, and CSN resection on the immunoreactivity of insulin receptors and GLP-1R in the CBs ( Figure 6 ). The presence of insulin receptors in the CBs was already described by our group ( Ribeiro et al, 2013 ), but herein, we showed that the insulin receptors are detected in the TH-positive glomus cells (red fluorescence – IR, green fluorescence – TH, Figure 6A ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…They are surrounded by a dense net of capillaries and penetrated by the sensory nerve ending of the carotid sinus nerve (CSN) a tiny branch of the glossopharyngeal nerve which does the connection from the CBs to the brainstem where their information is integrated [ 298 , 300 ]. In recent years, the CBs have been shown to have a key role in the control of peripheral glucose metabolism and insulin action, since it was shown that: (1) in animal models of dysmetabolism and in prediabetic patients, the CBs were overactivated, this being correlated with a state of insulin resistance and glucose intolerance [ 295 , 301 , 302 ]; (2) insulin, leptin, and GLP-1, known metabolic mediators involved in metabolic regulation, are capable of activating the CBs [ 295 , 296 , 303 , 304 ]; and (3) the resection or neuromodulation of the CSN prevents and reverses the pathological features associated with dysmetabolic states [ 295 , 297 , 301 ]. Considering the close association between metabolic and neurodegenerative disorders, and that the therapeutics that provide metabolic control have a huge impact on neurodegenerative processes, we anticipate that the modulation of the CBs might be a useful therapeutic strategy to improve metabolism, and therefore prevent and/or delay the progression of neurodegenerative disorders.…”
Section: Regulation Of Metabolic Function As a Prevention Of Neurodeg...mentioning
confidence: 99%